Answer: Our required values would be -10x+5, 2x+5 and -25.
Explanation:
Since we have given that
g(x) = -4x+5
and
h(x) = 6x
We need to find (g-h)(x) and (g+h)(x).
So, (g-h)(x) is given by
![g(x)-h(x)\\\\=-4x+5-6x\\\\=-10x+5](https://img.qammunity.org/2020/formulas/mathematics/college/fep52upz62hrjnt9g63zjdz3ip67gxtpl2.png)
and (g+h)(x) is given by
![g(x)+h(x)\\\\=-4x+5+6x\\\\=2x+5](https://img.qammunity.org/2020/formulas/mathematics/college/3s4fkay625ohgjkjx992qdleavbnqmtrsf.png)
and (g-h)(3) is given by
![-10(3)+5\\\\=-30+5\\\\=-25](https://img.qammunity.org/2020/formulas/mathematics/college/uniumtp4mdj57x6wrhy1yg2woitflpzhe2.png)
Hence, our required values would be -10x+5, 2x+5 and -25.